The role of spirituality and spiritual care in complementary and alternative medicine: A scoping review - Hoosen, Mujeeb; Roman, Nicolette Vanessa; Mthembu, Thuli Godfrey (Bangladesh Journal of Medical Science, 2021)
Background: Spirituality has become more prevalent in health professions other than complementary and alternative medicine (CAM). In CAM, spirituality appears to be part of a foundational component of the clinical practice, which is valued by many patients. Spirituality has gained popularity in healthcare education and practice; however, the contribution made by CAM remains minimal evidenced by the paucity of studies on the topic of spirituality in CAM. Therefore, there is need for a scoping review to: 1) to explore the focus and nature of research on spirituality in CAM; 2) to provide recommendations based on the relational aspects between spirituality and CAM. Methods: A scoping review was performed of all relevant articles found in Ebscohost (Academic Search Complete), Science Direct, and Scopus published between 2000 and 2019. This scoping review included two hundred and six studies, of these, twentytwo articles focussed on the role of spirituality in CAM. Results: These four themes were reported in the results: spirituality as a modality of CAM; patient perceptions of the role of spirituality and CAM; practitioner perceptions of the role of spirituality and CAM; and the role of spirituality and CAM in education and practice. Spirituality was considered an important component and was linked to culture, traditions and/or religious beliefs. The use of spirituality in CAM was especially linked to patients living with chronic disease such as diabetes, cardiac conditions and cancer. Spirituality seemingly facilitated health care and while patients expected spirituality healthcare advice from CAM practitioners most CAM practitioners felt ill equipped to deal with the topic appropriately. Conclusions: Overall, this scoping review highlights that the role of spirituality in CAM seem to be of value for both practitioners and clients within the CAM clinical setting. However, only a few practitioners include spiritual healthcare advice without clear guidelines. Consequently, this may compromise the holistic treatment, which so many patients expect within the CAM domain. Therefore, there is a need for the inclusion of spirituality in the CAM curriculum and guidelines for CAM practitioners. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.714-724